Nanoparticles of Cu2ZnSnS4 as performance enhancing additives for organic field-effect transistors. Issue 22 (12th May 2016) - Kevin, Punarja; Malik, Mohammad Azad; O'Brien, Paul; Cameron, Joseph; Taylor, Rupert G. D.; Findlay, Neil J.; Inigo, Anto R.; Skabara, Peter J.
Abstract : An investigation on the addition of oleylamine coated Cu2 ZnSnS4 nanoparticles in organic semiconductor solutions to fabricate organic field-effect transistors (OFETs). Abstract : The addition of oleylamine coated Cu2 ZnSnS4 (CZTS) nanoparticles to solutions of an organic semiconductor used to fabricate organic field-effect transistors (OFETs) has been investigated. The oligothiophene-based small molecule 5T-TTF and the polymer poly(3-hexylthiophene) (P3HT) were each applied in the transistors with various concentrations of CZTS (5–20%). Atomic force microscopy (AFM) was applied to characterise the surface morphology of the OFETs. The use of 5 and 10 wt% of the CZTS nanoparticles in 5T-TTF and P3HT solutions, respectively, appears to be a simple and effective way of improving OFET performance.